THE SUSTAINABLE DEVELOPMENT OF REGIONAL RURAL FINANCE IN CHINA - Dai XiXi; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
This study explores the sustainable development of rural regional finance in China based on the demand and supply of finance in rural areas, using Guizhou Province as an example. A survey was employed as the research methodology for this investigation. The main research technique employed for this study was a questionnaire. Five independent variables were selected to explore the impact on the sustainable development of regional finance in rural China based on the supply and demand of rural finance, namely cost of funds, credit demand, government regulations, financial facilities, and accessibility to funds. The cost of funds and credit demand are significantly related to the sustainable development of regional rural finance. In contrast, government regulations, financial facilities, and accessibility to funds are not significantly related to the sustainable development of regional rural finance. The results of this study help governments, practitioners and citizens to understand the sustainable development of regional rural finance in China and the factors that are significantly related to the sustainable development of regional rural finance.